Race to the Bottom: an Introduction to Gig Economy based on Moral Economy in Islam Perspective (State Islamic Institute of Kudus (IAIN Kudus), 2020)
Gig economy has recently circling in the society in the digital era. It has been a result of risk society as described by Beck in his book. Though researches have been made by Standing, Stephany dan Prassl to address the various risk exposed by it onto society, there is little evidence society would not expose to its excesses. This writing is made as part of research in gig economy that argues the race to the bottom of gig economy has contributed to society. The findings include how exploitation, job insecurity, mental and health crisis are generated from informalisation of works in gig mode of economy. The most essential thing is how Islam offer the new mode of economy based on its fundamental views of social welfare and individual interest based on moral economy as a solution to the race of the bottom occurring in gig economy.